DARI BIASA MENJADI LUAR BIASA: VICTORIA’S SECRET - Resti Nurfaidah (LITERASI: Indonesian Journal of Humanities, 2013)
Bra is one of the basic needs of women fashion. The history of bra has been unbelievably reached up to two hundred years old while during the period, it was fulfilled with ups and downs experiences. They have been confronted by the pros-contra reactions. The contra said that being multiple layers of woman dress seemed to be persecution. A series of inventions emerged as part of the improvements in making the bra shape getting better and more comfortable. They intended to burn those bras, but by the security guards helps, it didn’t happen anyway. They, at the end, threw those bras into the garbage can. This article explores the connection of bra status, before and after, the performance of the Victoria’s secret. Victoria’s secret is considered a leading pioneer in bra innovations using others material on bra surfaces. Its innovations have involved the great combination of fabrics, laces, comfortable, and using prime germs, such as sapphire, diamonds, or white and yellow gold meta, also the improvement of the status of the bra itself. Victoria’s Secret will be the trendsetter in the underwear world. The analysis shows that Victoria’s Secret seeks to restore femininity to strengthen themselves against of the high pressures of masculinity in the public domain by empowering their own weak sides as weapon. Keywords: bra, Victoria’s Secret, innovation, and values